ASSOCIATION TYPE 2 DIABETES MELLITUS AND ALZHEIMER DISEASE : A SYSTEMATIC REVIEW - Persson Jeffry, Erick (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
The International Diabetes Federation (IDF) reports that diabetes affects one in ten people throughout the world, and that insulin-resistant type 2 diabetes mellitus (T2DM) accounts for 90 percent of all cases of diabetes. According to findings from epidemiology research, the pathophysiology and clinical patterns of Alzheimer's disease and type 2 diabetes are similar. Insulin resistance is a hallmark of both illnesses. The pathogenesis differentiates between inflammatory, metabolic, and zinc-deficient variants of the condition. Alzheimer's disease is associated with both type 2 diabetes and prediabetes, often known as metabolic syndrome. Due to the fact that Alzheimer's disease shares many pathophysiological similarities with diabetes, it is sometimes referred to as type 3 diabetes. A primary focus of dementia research is insulin resistance, which impairs cognitive function and contributes to the development of dementia. IGF has an effect on cognition as well. The chance of acquiring T2DM rises with age, much like the risk of developing Alzheimer's disease, and T2DM also raises the risk of developing dementia in general, specifically Alzheimer's disease. Both T2DM and AD are chronic and complex diseases, and both show evidence that oxidative stress and inflammation play a role in the progression of the diseases. Despite the fact that T2DM is primarily a peripheral disorder and AD is a disease of the central nervous system, the two diseases share some similarities.